Circular Economy Integration in Supply Chain Management: A Strategic Response to SDG 12 - Mohammad Ridwan Rumasukun (Manunggal Halim Jaya, 2026)
This study examines the integration of circular economy (CE) principles into supply chain management (SCM) as a strategic response to Sustainable Development Goal 12 (SDG 12) on responsible consumption and production. Using a qualitative literature-based approach, the research synthesizes recent theoretical advancements and empirical evidence to explore how CE reshapes supply chain structures, operational processes, and sustainability outcomes across global industries. The findings reveal that CE provides a regenerative framework that redefines traditional linear systems by promoting closed-loop material flows, eco-design, reverse logistics, and collaborative multi-stakeholder networks. The study further identifies key enablers—including digital technologies, regulatory pressures, and leadership commitment—that enhance the feasibility and scalability of circular supply chain practices, while highlighting persistent barriers such as infrastructural limitations, financial constraints, and fragmented policy environments. The analysis demonstrates that CE integration not only contributes to environmental performance and resource efficiency but also strengthens organizational resilience, innovation capacity, and long-term competitiveness. From a theoretical perspective, the study advances sustainability and operations management literature by illustrating how CE functions as a structural mechanism for achieving SDG 12. From a managerial perspective, the results underscore the need for strategic alignment, investment in digital capabilities, and cross-sector collaboration to support effective circular transitions. Overall, the study positions circular supply chain management as a critical pathway for accelerating global sustainability transformations and calls for continued research and policy coordination to deepen and institutionalize circular practices.